Determin Minat Beli Ulang Mie Gacoan Bekasi dengan Labelisasi Halal Sebagai Variabel Moderasi - Sarmila, Lia; Listian Indriyani Achmad; Ainulyaqin, MH; Sakum; Sukron Mamun (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the effect of price and service quality service quality on repurchase interest in Gacoan Noodle products with halal labeling as a moderating variable. As a moderating variable. This research method uses SPSS 24 software with a sample of 100 respondents. Taken as many as 100 respondents. The data analysis method used is path analysis. The results showed that the value between price and Halal Labeling has a previous value (1.966) and a moderating value (1.966). Before (1.966) and has a value comparison (-2.978) then it can be concluded that the halal labeling variable is able to moderate the effect of the Price variable on the.Repurchase Interest variable. And the value between Service Quality and Halal Labeling has the previous value (0.513) and has a value comparison (0.426), so it can be concluded that the variable Halal labeling is not able to moderate the influence of the Service Quality variable on the Repurchase Interest variable.